1968
DOI: 10.1177/002221946800100901
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Pathological Findings in a Child with a Developmental Learning Disability

Abstract: Many professionals have deplored the fact that there have been no published post mortem findings of children with developmental learning disabilities. To our knowledge this is the first case history offered to the literature. It is presented from an inter-disciplinary approach thus involving various professional efforts and evolutionary thoughts. The Journal is very proud to publish this manuscript. Dr. Drake and his evaluation team have performed a great service for the field of learning disabilities.—C.C.E.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
3

Year Published

1979
1979
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(37 citation statements)
references
References 4 publications
2
32
0
3
Order By: Relevance
“…Although some later studies have highlighted the fact that considerable variability in callosal anatomy is present, little information is currently available on possible differences in callosal anatomy in dyslexies and controls. The only report of callosal anatomy in dyslexies is the early case report by Drake (1968) who found thinning of the callosum at postmortem in a boy with reading disability.…”
Section: Discussionmentioning
confidence: 99%
“…Although some later studies have highlighted the fact that considerable variability in callosal anatomy is present, little information is currently available on possible differences in callosal anatomy in dyslexies and controls. The only report of callosal anatomy in dyslexies is the early case report by Drake (1968) who found thinning of the callosum at postmortem in a boy with reading disability.…”
Section: Discussionmentioning
confidence: 99%
“…Reports by Drake (1968), Galaburda and Kemper (1979), and Galaburda and Eidelberg (1982) provide more information about the correlated neurodevelopmental deficits. Drake (1968) reported on the first autopsy of a learning-disabled child's brain. He noted an abnormal convolutional pattern in both parietal lobes.…”
Section: Cytoarchitectonic Studiesmentioning
confidence: 99%
“…Nevertheless, recent reviews suggest an underlying central nervous system (eNS) dysfunction for this disorder (4,13,28). The most direct evidence for a neurological basis for reading disabilities has come from postmortem cytoarchitectonic (29)(30)(31)(32)(33) and imaging (34) studies of brains of dyslexic individuals, which have demonstrated cortical abnormalities and variations in structural symmetry. The anomalies observed, although present in a small number of often poorly documented clinical studies, are thought to be consistent with reading failure (2,13).…”
mentioning
confidence: 99%